Surface Oxidation Of CU Extracted From Electronic Waste For CUO Nanowires Formation And Their Use To Reduce CR(VI) - Yong, Hui Sin (Universiti Sains Malaysia, 2022)
Cr(VI) is considered a toxic heavy metal and will affect the health of those who consumed it. It can enter the ecosystem from various fields’ wastewater. In this study, the capability of CuO NWs for the reduction of Cr(VI) to Cr(III) was investigated. The Cu was firstly extracted from WPCB by leaching and electrodeposition of the Cu layer on Ti foil. The concentration of Cu present in leaching and digested solution were characterized using ICP-MS. The CuO NWs were fabricated by thermal oxidizing the electrodeposited Cu layer at temperature between 300 to 500 'C. All samples were tested for photoreduction under sunlight for 90 minutes. The CuO NWs were characterized using FESEM with EDX, XRD and HRTEM. The oxidation parameters investigated were surface roughness, oxidation temperature and oxidation duration. Oxidation at 350'C was conducted to investigate the growth of NWs on different surface roughness of Cu layer. The density of the NWs grown on the roughest surface was non-uniform with average length and diameter of 1015.3 nm and 34.2 nm, hence resulting in the least reduction of Cr(VI) which was 44 %. For the effect of temperature, the NWs formed at the temperature range of 300 – 500'C had length and diameter between 1798.31 – 539.5 nm and 53.66 – 20.9 nm. 47.5 % Cr(VI) reduction was achieved for sample oxidized at 500'C. Various oxidation duration was studied at 400'C ranging from 30 to 120 minutes. With prolonged oxidation duration, the length and diameter of NWs formed increased. 35 % Cr(VI) reduction was achieved for sample oxidised for 120 minutes.